Implementation of the AU AI Strategy: What Role Can R/NRENs Play - Ogot, Madara (UbuntuNet Alliance for Research and Education Networking, 2025)
The African Union (AU) Artificial Intelligence (AI) Strategy (2024) aims to catalyse inclusive AI-enabled growth and safeguard sovereignty, individual and organisational rights. National Research and Education Networks (NRENs) and Regional Research and Education Networks (RRENs) in Africa have the potential to transform fragmented AI initiatives, especially those anchored around the research and education (R&E) sectors, into coherent, layered architectures that support responsible, inclusive, and sustainable AI development and use across the continent. R/NRENs today have the opportunity to reinvent themselves by becoming key enablers of the development and use of AI in Africa, especially in the R&E sectors, in support of national, regional and the AU’s AI strategies. Potential areas of engagement aligned to the AU AI Strategy are presented.
Keywords: Africa; Artificial Intelligence; NREN; RREN